1999
DOI: 10.3109/08916939908994766
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Anti-β2 Glycoprotein I Antibodies in Patients with Ischemic Heart Disease

Abstract: Ischemic cardiac manifestations have been reported in a various percentage of patients with anti-phospholipid antibodies. As concerns the relationship between anti-beta2 glycoprotein I antibodies (anti-beta2-GPI) and ischemic heart disease (IHD), it was investigated in only one coronary primary prevention study. We investigated the prevalence of anti-beta2-GPI in a well characterized group of patients with different clinical manifestation of IHD. Sera from 37 patients (mean age 62.7 +/- 9.9) with IHD (20 with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
2
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 19 publications
1
16
2
1
Order By: Relevance
“…We reported a slightly different study where positive antib2GPI of any Ig class were detected in 11% of nonselected RA patients (Ambrozˇicˇet al, 2002a). Farsi et al (1999) related IgG anti-b2GPI with coronary atherosclerosis. However, data from the Honolulu heart program (Brey et al, 2001) showed insignificant frequency of IgG anti-b2GPI in patients with atherosclerosis compared to controls.…”
Section: Discussionmentioning
confidence: 82%
“…We reported a slightly different study where positive antib2GPI of any Ig class were detected in 11% of nonselected RA patients (Ambrozˇicˇet al, 2002a). Farsi et al (1999) related IgG anti-b2GPI with coronary atherosclerosis. However, data from the Honolulu heart program (Brey et al, 2001) showed insignificant frequency of IgG anti-b2GPI in patients with atherosclerosis compared to controls.…”
Section: Discussionmentioning
confidence: 82%
“…In a recent study by Veres et al, 42 the authors report that the frequency and titers of anti-␤ 2 -GPI antibodies were significantly higher in patients with acute coronary syndromes than in controls, data that are consistent with previous studies on patients with stable and unstable angina. 43 Building on these observations, de Laat et al 44 developed an assay to discriminate between ␤ 2 -GPI antibody-dependent LA and ␤ 2 -GPI-independent LA activity. They subsequently applied this assay to a retrospective cohort of 198 patients with either systemic lupus erythematosus (SLE; nϭ176), lupus-like disease (nϭ16), or primary antiphospholipid syndrome (nϭ6) and found that among the 58 patients with LA, 25 had ␤ 2 -GPI antibody-dependent LA activity.…”
Section: Antiphospholipid Antibodiesmentioning
confidence: 99%
“…Evidence suggesting a relationship between anti-b2GPI and the risk of arterial and venous thrombosis in these patients is not so abundant and uniform results have not been found. The predominance of isotype IgG, or IgM, or both, or none has been reported in different groups of patients with different localization of the thrombosis (Forastiero et al, 1999;Zanon et al, 1999;Farsi et al, 1999;Galli et al, 2000;Brey et al, 2001;Previtali et al, 2002). Evidently, additional data focused on strictly defined subgroups of patients are needed.…”
Section: Article In Pressmentioning
confidence: 88%